Faktor-Faktor Keuangan dan Komite Audit Dalam Meningkatkan Nilai Perusahaan (Jurnal Kendali Akuntansi, 2025)
Firm value is the ratio between stock price and book value. The high value of the company attracts investors to invest their capital in the company, it indicates that the company has good prospects in the future. The purpose of this study was to determine the effect of the current ratio, debt to equity ratio, total asset turnover and audit committee on firm value. The population is manufacturing companies in the food and beverage sector which are listed on the Indonesia Stock Exchange (IDX) in the 2016-2019 financial statements. The sample was determined by purposive sampling technique with certain criteria and obtained a sample of 17 companies. This research uses multiple linear regression analysis method assisted by SPSS Ver.26 program. The results of this study indicate that the current ratio has a negative and significant effect on firm value, while the debt to equity ratio, total asset turnover and audit committee have no effect on firm value.